Hypertriglyceridemia-induced Acute Pancreatitis Treated with Insulin Therapy: A Case series - Nizhu , Lutfun Nahar; Anam, Ahmed Mursel (Bangladesh Journal of Medicine, 2024)
Hypertriglyceridemia is a condition where high levels of triglycerides in the blood can cause recurrent episodes of acute pancreatitis. The risk of acute pancreatitis becomes significant when serum triglyceride levels exceed 1000 mg/dL. Although the severity of hypertriglyceridemia-induced acute pancreatitis may be related to higher HTG levels in the early stages, the overall clinical outcomes are similar to other causes. The initial management of HTG-AP differs from routine recommendations and poses additional diagnostic and therapeutic challenges. This retrospective case series describes our experience with hypertriglyceridemia-induced acute pancreatitis at our acute medicine department and emphasizes the role of insulin therapy in its management. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 180